2017
DOI: 10.18632/oncotarget.17136
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-29b in carcinoma associated fibroblasts promotes cell growth and metastasis of breast cancer

Abstract: Carcinoma associated fibroblasts (CAFs) play important roles in breast cancer development and progression. Recent studies show that microRNAs (miRNAs) are the main regulators in CAFs. MiR-29b is one of the significant down-regulated miRNAs in CAFs from the miRNA screening. The role of miR-29b in the interaction between CAFs and breast cancer is still unclear. In the present study, we investigated the effects of CAFs on breast cancer cell proliferation and metastasis regulated by miR-29b. We found that fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 36 publications
(32 reference statements)
2
41
0
Order By: Relevance
“…Wu et al hinted that miR-29 functioned as a tumor suppressor in breast cancer cells by down-regulation of B-Myb [29]. Liu et al announced that miR-29b accelerated breast cancer cells cell growth and metastasis [30]. Nonetheless, whether miR-29 affected the biological processes of breast cancer cells under Sino administration remains vague.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al hinted that miR-29 functioned as a tumor suppressor in breast cancer cells by down-regulation of B-Myb [29]. Liu et al announced that miR-29b accelerated breast cancer cells cell growth and metastasis [30]. Nonetheless, whether miR-29 affected the biological processes of breast cancer cells under Sino administration remains vague.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lower miR-29b expression in CAFs can accelerate metastasis by activating the p38-STAT1 pathway in breast cancer cells and up-regulating CXCL14 and CCL11 in CAFs. Additionally, STAT1 increases expression of CXCL14 and CCL11 at the transcription level [62]. Kaplan-Meier curves revealed that high CXCL14 mRNA levels were correlated with favorable relapse-free survival (RFS) in all types of BC patients, and high transcription levels of CXCL14 conferred an overall survival (OS) advantage in all BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer associated fibroblasts (CAF) play an important part in sustaining and protecting tumor cells and may lend themselves to new unconventional approaches to cancer therapy [123]. CAFs co-cultured with breast cancer cells produce high levels of CCL11 and CXCL14 chemokines, which stimulate cancer cell proliferation and resistance to paclitaxel by activating p38 -STAT1 signaling [67,124]. Triple-negative breast cancer often shows overexpression of interleukin-1 receptor-associated kinase 1 (IRAK1), and paclitaxel treatment activates IRAK1, which increases the stemness of cancer cells and confers resistance to paclitaxel treatment.…”
Section: P38 Enhancing Resistance To Targeted Therapies and Chemothermentioning
confidence: 99%